Seven Segment Display Circuit Simulation using Electronics Workbench - Praja, Muhamad Januar Indra; Saputra, Renda Sandi (Research Collaboration Community (Rescollacom), 2022)
A seven segment display, or in Indonesian it is called a seven segment display, is an electronic device consisting of segments that are used to display decimal numbers or numbers. This journal will explain how to simulate a seven segment display circuit using computer software called Electronics Workbench. This simulation is done to help understand how a seven segment display circuit can work, and because this is a simulation, there is no need to be afraid of failure, or making mistakes. This simulation is done by connecting a seven segment display with a 74 series Digital IC, you can use a 7447 or 7448 IC, because the function is still the same, and the IC formation is still the same, and is suitable for connecting seven segment displays. Then the IC is controlled via a switch / button that is connected directly to the IC, and the switch and IC are also connected to a power source, so that the circuit simulation can run. The results of this simulation show that the simulation can be done well in the Electronics Workbench software, can be a medium of learning about how seven segment displays work, and so that we can more easily understand how electronic devices work.